Accelerated thermal cycle and chemical stability testing of polyethylene glycol (PEG) 6000 for solar thermal energy storage - Sharma R.K.; Ganesan P.; Tyagi V.V.; Mahlia T.M.I. (Elsevier B.V., 2023)
Chemical analysis; Differential scanning calorimetry; Economic analysis; Heat storage; Latent heat; Melting point; Phase change materials; Polyethylene glycols; Polyethylenes; Reliability analysis; Solar energy; Thermal cycling; Thermal energy; Accelerated thermal cycles; Compositional stability; Differential scanning calorimeters; Latent heat of fusion; Organic phase change material (O-PCM); Techno- economic analysis; Thermal energy storage systems; Thermal reliability; Chemical stability